Peran Kementerian Agama dalam Mengentaskan Kemiskinan Ekstrim di Bali Menggunakan Metode Analisis SWOT: Strategi dan Implikasi Kebijakan - Ariawan, I Pande Made (JURNAL ILMIAH GEMA PERENCANA, 2024)
In 2023, significant meeting was held in Bali by the Provincial and District/City Poverty Reduction Coordination Team. The aim was to assess the progress of poverty reduction programs, devise integrated strategies across sectors, and expedite poverty alleviation efforts in the region. Despite a relatively low national poverty rate of 4.25%, Bali has seen stagnation above 4% over the past five years, signaling the need for fresh collaborative strategies. Aligned with the Sustainable Development Goals and President’s directive to eradicate extreme poverty by 2024, it’s crucial to engage the national team, collaborate with Bali Province MDA, and incorporate local wisdom policies. Poverty data is presented using a basic needs approach, encompassing food and non-food poverty lines, along with micro and macro data. The analysis reveals an uptick in poverty during the pandemic, followed by a recovery. The non-food poverty line increasingly influences poverty conditions. Five key food non-food commodities contributing to Bali’s poverty line have been identified. The province’s poverty depth and severity are also reported. The analysis includes income inequality and population expenditure distribution, concluding that income inequality in Bali is low by World Bank standards. Despite pockets of extreme poverty in some districts, the overall level is relatively low. Social assistance and funding have been distributed, and Bali’s concept of poverty encompasses economic, sociocultural, and environmental aspects.